BACKGROUNDS OF FORMATION OF INDUSTRIAL ARTS EDUCATION OF GALICIA IN HISTORICAL AND PEDAGOGICAL CONTEXT THE END OF XIX CENTURY - Synyshyn, Lily O. (Educological discourse, 2015)
In exploration highlights and reasonable conditions becoming art-industrial education in Galicia historical and pedagogical context of the late nineteenth century. Industrial Arts Education is seen as an integrated phenomenon that is the result of social and cultural experiences of people subject to assimilation worldview. Following the completion of theoretical sources, materials stored in the collections of archives, the influence of socio-economic, organizational, educational, aesthetic and cultural conditions to develop the content of artistic and industrial education, the development of networks of artistic and industrial schools in certain territorial and chronological limits, especially the training of teachers for these schools, the relationship between the state of art and industrial education, social, economic and cultural challenges of the time are found. The article deals with the peculiarities of the Lviv Art and Industrial School as a cultural and educational center of art and industrial education Galicia in the late nineteenth century in terms of European models of intercultural environment.